Building mud castles: a perspective from brick-laying termites - Nikita Zachariah (Nature Portfolio, 2017)
Abstract Animal constructions such as termite mounds have received scrutiny by architects, structural engineers, soil scientists and behavioural ecologists but their basic building blocks remain uncharacterized and the criteria used for material selection unexplored. By conducting controlled experiments on Odontotermes obesus termites, we characterize the building blocks of termite mounds and determine the key elements defining material choice and usage by these accomplished engineers. Using biocement and a self-organized process, termites fabricate, transport and assemble spherical unitary structures called boluses that have a bimodal size distribution, achieving an optimal packing solution for mound construction. Granular, hydrophilic, osmotically inactive, non-hygroscopic materials with surface roughness, rigidity and containing organic matter are the easiest to handle and are crucial determinants of mass transfer during mound construction. We suggest that these properties, along with optimal moisture availability, are important predictors of the global geographic distribution of termites.